Obraz kobiety w twórczości śpiewanej okresu staropolskiego = The image of women in old Polish songs - Jabłońska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article covers the period from the Middle Ages to the Partitions of Poland. It attempts at presenting the different incarnations and roles of women as well as the topoi, archetypes and stereotypes found in song lyrics understood as literary-musical works. One of the most emphasised archetypes is the one of a woman-mother. It originates from Mary, the mother of Jesus, an advocate and mediator, the ideal of beauty and women's character who also shows very human emotions. As it is said in soldier and knight songs, she is also referred to as the guardian of Poland, who helps to defeat enemies.
Keywords: kobieta; Polska - historia - do 16 w.